2019
DOI: 10.31219/osf.io/3ezhc
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bucher et al. Personality traits and treatment outcomes meta-analysis

Abstract: Personality traits have been hypothesized to be clinically useful for diagnosis, client conceptualization, treatment planning, as well as for predicting treatment outcomes. Although several studies examined the relation between personality traits and specific therapy outcomes, this literature has not yet been systematically reviewed. Thus, the purpose of the current study was to investigate the relations between personality traits and various therapeutic outcomes. Traits were organized via the domains of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 64 publications
1
4
0
Order By: Relevance
“…The results of this study add to a growing body of literature highlighting differences in attitudes of obstetric and neonatal health care professionals involved in the complex scenario of extremely preterm birth. [24][25][26] Similar to previous research, our findings suggest that some obstetricians may be less inclined toward intervention at the extremes of viability than some neonatologists, potentially as this area of care is less visible to obstetricians than neonatologists. 27,28 As with previous research by some of us, we identified a more interventionalist approach among some neonatal nurses, potentially reflecting a gradual integration and acceptance of advanced medical technology that now forms part of the routine care of extremely preterm infants.…”
Section: Jama Network Open | Pediatricssupporting
confidence: 84%
“…The results of this study add to a growing body of literature highlighting differences in attitudes of obstetric and neonatal health care professionals involved in the complex scenario of extremely preterm birth. [24][25][26] Similar to previous research, our findings suggest that some obstetricians may be less inclined toward intervention at the extremes of viability than some neonatologists, potentially as this area of care is less visible to obstetricians than neonatologists. 27,28 As with previous research by some of us, we identified a more interventionalist approach among some neonatal nurses, potentially reflecting a gradual integration and acceptance of advanced medical technology that now forms part of the routine care of extremely preterm infants.…”
Section: Jama Network Open | Pediatricssupporting
confidence: 84%
“…The shape of the resulting leakage spectrum can be expressed as a kind of convolution between the harmonic coefficients of the crossing moment maps and of the dust component map (see Ref. [33] for an analytical explanation of this power law). This spectral shape is problematic on very large scales, for example near the reionization bump, because the ratio of the bandpass mismatch to the white noise component of the detector noise (having an η ≈ 0 spectrum) increases toward lower multipole number .…”
Section: Resultsmentioning
confidence: 99%
“…= 3 MeV; with a recent experiment, measured energies are now extending down to the Gamow window. At typical carbon shell burning temperatures, T = 1.1 − 1.3 GK, the uncertainty is less than 40%, and reduced to 20% at T = 1.9 − 2.1 GK, which is relevant for explosive C burning (Bucher et al 2015).…”
Section: Uncertainties In the Relevant Reaction Ratesmentioning
confidence: 95%